Imaging in spinal posterior epidural space lesions: A pictorial essay - Gala, Foram B; Aswani, Yashant (Indian Journal of Radiology and Imaging, 2016)
Spinal epidural space is a real anatomic space located outside the dura mater and within the spinal canal extending from foramen magnum to sacrum. Important contents of this space are epidural fat, spinal nerves, epidural veins and arteries. Due to close proximity of posterior epidural space to spinal cord and spinal nerves, the lesions present with symptoms of radiculopathy and/or myelopathy. In this pictorial essay, detailed anatomy of the posterior epidural space, pathologies affecting it along with imaging pearls to accurately diagnose them are discussed. Various pathologies affecting the posterior epidural space either arising from the space itself or occurring secondary to vertebral/intervertebral disc pathologies. Primary spinal bone tumors affecting the posterior epidural space have been excluded. The etiological spectrum affecting the posterior epidural space ranges from degenerative, infective, neoplastic - benign or malignant to miscellaneous pathologies. MRI is the modality of choice in evaluation of these lesions with CT scan mainly helpful in detecting calcification. Due to its excellent soft tissue contrast, Magnetic Resonance Imaging is extremely useful in assessing the pathologies of posterior epidural space, to know their entire extent, characterize them and along with clinical history and laboratory data, arrive at a specific diagnosis and guide the referring clinician. It is important to diagnose these lesions early so as to prevent permanent neurological complication.
Keywords: Compressive myelopathy; epidural space; magnetic resonance imaging; posterior epidural abscess; posterior epidural hematoma